Combined Endoscopic and Laparoscopic Management of Postcholecystectomy Mirizzi Syndrome from a Remnant Cystic Duct Stone: Case Report and Review of the Literature. (7th March 2016) - Amin, Arpit; Zhurov, Yuriy; Ibrahim, George; Maffei, Anthony; Giannone, Jonathan; Cerabona, Thomas; Kaul, Ashutosh
Abstract : Mirizzi syndrome has been defined in the literature as common bile duct obstruction resulting from calculi within Hartmann's pouch or cystic duct. We present a case of a 78-year-old female, who developed postcholecystectomy Mirizzi syndrome from a remnant cystic duct stone. Diagnosis of postcholecystectomy Mirizzi syndrome was made on endoscopic retrograde cholangiography (ERCP) performed postoperatively. The patient was treated with a novel strategy by combining advanced endoscopic and laparoscopic techniques in three stages as follows: Stage 1 (initial presentation): endoscopic sphincterotomy with common bile duct stent placement; Stage 2 (6 weeks after Stage 1): laparoscopic ultrasonography to locate the remnant cystic duct calculi followed by laparoscopic retrieval of the calculi and intracorporeal closure of cystic duct stump; Stage 3 (6 weeks after Stage 2): endoscopic removal of common bile duct stent along with performance of completion endoscopic retrograde cholangiogram. In addition, we have performed an extensive review of the various endoscopic and laparoscopic management techniques described in the literature for the treatment of postcholecystectomy syndrome occurring from retained cystic duct stones.